2018
DOI: 10.3171/2018.5.peds18120
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic laser ablation for nonlesional cingulate epilepsy: case report

Abstract: Stereotactic laser ablation (SLA) is being increasingly used to treat refractory focal epilepsy, especially mesial temporal lobe epilepsy. However, emerging evidence suggests it can be used for extratemporal lobe epilepsy as well.The authors report the case of a 17-year-old male who presented with refractory nocturnal seizures characterized by bilateral arms stiffening or rhythmic jerking lasting several seconds. Semiology suggested an epileptogenic zone close to one of the supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…One study that was documented as a video supplement on YouTube reported utilization of LiTT for anterior 2/3 callosotomy (using 3 trajectories/laser applicators) in a 17-year old female patient with a history of Lennox-Gastaut syndrome [37]. Two studies reported stereotactic EEG-guided laser thermotherapy in patients with MRI-nonlesional epilepsies [19,36]. Somewhat unexpectedly, two studies did not define the underlying etiology more closely for a total of 11 patients [5,31].…”
Section: Indication (Underlying Etiologies)mentioning
confidence: 99%
“…One study that was documented as a video supplement on YouTube reported utilization of LiTT for anterior 2/3 callosotomy (using 3 trajectories/laser applicators) in a 17-year old female patient with a history of Lennox-Gastaut syndrome [37]. Two studies reported stereotactic EEG-guided laser thermotherapy in patients with MRI-nonlesional epilepsies [19,36]. Somewhat unexpectedly, two studies did not define the underlying etiology more closely for a total of 11 patients [5,31].…”
Section: Indication (Underlying Etiologies)mentioning
confidence: 99%
“…20,32 It has also been applied to mesial temporal lobe epilepsy 10,11,34,36 and localized focal epilepsy. 19,37 Few studies have suggested that LITT may be effective in performing corpus callosotomy with acceptable risk and reduced surgical morbidity. Here, we pre sent our efforts in the continued innovation of less invasive neurosurgical treatment with a retrospective case series of corpus callosotomy performed with LITT in 10 patients at our institution.…”
mentioning
confidence: 99%
“…LCA is multiple, and few solitary neoplasms were reported. To date, imaging examination cannot determine whether the lesion is benign or malignant because some other neoplasms of the spleen such as Kaposi sarcoma, [ 10 ] angiosarcoma hemangiomatosis, [ 11 ] hamartoma, [ 12 ] lymphoma, [ 13 ] hemangioendothelioma, and angiosarcoma, [ 14 , 15 ] share similar appearance to LCA. In addition, no correct diagnosis of LCA can be established before surgery.…”
Section: Discussionmentioning
confidence: 99%